Synergy Between Two Chimeric Lysins to Kill Streptococcus pneumoniae - Vázquez, Roberto; García, Pedro (Frontiers in Microbiology, 2019)
Phage lysins constitute a new generation of antimicrobials that are becoming a promising alternative and complementation to current antibiotic therapies, which are nowadays called into question by the increasing numbers of multiresistant bacteria. Streptococcus pneumoniae is a leading human pathogen causing serious infectious diseases in children and adults. Within the host-parasite interplay system of pneumococcus and its phages, several antipneumococcal lysins have been described and, among them, chimeric lysins Cpl-711 and PL3 stand out for their potent bactericidal activities. Here, evidence is presented on the synergistic cooperation of the catalytically diverse lysins Cpl-711 and PL3 in different assays, like purified cell wall enzymatic degradation, in vitro bacterial cell growth inhibition, and killing of both planktonic and biofilm grown cells. Synergy between Cpl-711 and PL3 has been shown to reduce the amount of enzyme necessary to inhibit growth in checkerboard assays with a sum of fractional inhibitory concentrations ≤ 0.5 for all pneumococcal strains tested, while also significatively increasing bactericidal effect by  2 logs with respect to the sum of activities of Cpl-711 and PL3 individual treatments. Moreover, the combination of these two lysins showed synergy in an adult zebrafish model of pneumococcal infection. This study consolidates the possibility of formulating highly efficient and synergistic antibacterial enzymes that could improve our ability to fight multiresistant bacterial infections.